STUDENTS’ ABILITY IN USING RESTRICTIVE AND NONRESTRICTIVE ADJECTIVE CLAUSE - Kristian Burhan (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The purpose of this research to know the second year students’ ability in using restrictive and non-restrictive adjective clause. Design of this research was descriptive research. The data of this research were gotten by distribution of grammar test. The result of this research showed that the students’ ability in using restrictive and non-restrictive adjective clause in sentence in average classification. It is proven that the mean score of students’ ability in using restrictive and non-restrictive adjective clause in sentences was 11.27 or 37.57%.